Chemical-resistant silver plating paste for low-temperature co-fired ceramic and preparation method of chemical-resistant silver plating paste
By using barium titanate, titanium oxide and zinc oxide as nanoadditives in the silver paste of low-temperature co-fired ceramics as nanoadditives, combined with specific composition glass frit and binder, the microcracks and warping problems caused by different shrinkage rates between materials during the sintering process of silver paste are solved, and chemical resistance is significantly improved, and the stability and service life of the device are enhanced.
Patent Information
- Application Number
- CN202411890401.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-21
AI Technical Summary
The existing silver paste used for low-temperature co-fired ceramics has micro cracks and warping due to different shrinkage rates between materials during the sintering process, and has weak chemical resistance, which affects the stability and service life of the device.
The combination of barium titanate, titanium oxide and zinc oxide is used as nano additives, combined with a specific composition of glass frit and binder, and by controlling the shrinkage rate and network structure during the sintering process, electroless silver plating paste is prepared.
It effectively solves the microcracks and warping problems caused by different shrinkage rates between materials during sintering, and significantly improves the chemical resistance of silver paste, enhancing the stability and service life of the device.
Smart Images

Figure BDA0005200514350000021 
Figure BDA0005200514350000041 
Figure BDA0005200514350000051
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic materials, and in particular, relates to a chemical-resistant silver plating paste for low-temperature co-fired ceramics and a preparation method thereof. Background Art
[0002] With the rapid development of electronic technology, low-temperature co-fired ceramic technology has been widely used in many fields such as electronic packaging, microwave devices, sensors, etc. In the LTCC process, silver paste is one of the most critical materials. It is mainly used to realize the electrical connection between the ceramic layer and the circuit layer and the signal transmission function. However, there are still many technical problems that need to be solved in the current silver paste used for LTCC. For example, during the sintering process, due to the significant difference in the shrinkage rate between the silver paste and the ceramic material, uneven internal stress is easily generated inside the material, resulting in the formation of microcracks. Microcracks not only destroy the integrity of the material, but also have a negative impact on its electrical properties. Severe shrinkage rate differences can also cause the material to warp and deform, making the prepared LTCC device unable to meet the high-precision assembly requirements, greatly limiting its application in electronic equipment with high dimensional accuracy requirements. In addition, the chemical resistance of existing silver pastes is generally weak, which leads to the LTCC device being corroded by contact with various chemicals in the actual application environment, resulting in the stability and service life of the product device being reduced, and increasing maintenance costs and use risks.
[0003] Therefore, developing a silver paste for low-temperature co-fired ceramics that can effectively solve the problems of microcracks and warping caused by different shrinkage rates between materials and significantly improve chemical resistance has extremely important practical significance and broad market prospects. Summary of the invention
[0004] The object of the present invention is to provide a chemical-resistant silver plating paste for low-temperature co-fired ceramics and a preparation method thereof, which solves the problems of microcracks, warping and poor chemical resistance caused by different shrinkage rates between materials in the prior art.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A chemical-resistant silver plating paste for low-temperature co-fired ceramics, the chemical-resistant silver plating paste comprising the following raw materials in parts by weight:
[0007]
[0008] As a preferred technical solution of the present invention, the particle size of the silver powder is 6-10 μm.
[0009] As a preferred technical solution of the present invention, the glass material includes boron trioxide, silicon dioxide, bismuth trioxide, aluminum trioxide, strontium oxide, lanthanum oxide, barium oxide, and strontium carbonate.
[0010] Furthermore, the mass ratio of boron trioxide, silicon dioxide, bismuth trioxide, aluminum trioxide, strontium oxide, lanthanum oxide, barium oxide and strontium carbonate is 15-20:10-15:4-6:3-5:2-3:1-2:0.5-0.8:0.5-1.
[0011] As a preferred technical solution of the present invention, the nano additives include barium titanate, titanium dioxide and zinc oxide.
[0012] Furthermore, the mass ratio of the barium titanate, titanium dioxide and zinc oxide is 3-8:4-6:3-6.
[0013] Furthermore, the particle sizes of the barium titanate, titanium dioxide and zinc oxide are all 80-100 nm.
[0014] As a preferred technical solution of the present invention, the binder includes polyvinyl pyrrolidone and polyacrylate.
[0015] Furthermore, the mass ratio of the polyvinyl pyrrolidone to the polyacrylate is 1:1-1.4.
[0016] As a preferred technical solution of the present invention, the solvent includes butyl carbitol and terpineol.
[0017] Furthermore, the mass ratio of butyl carbitol to terpineol is 3-4:1-2.
[0018] A method for preparing a chemical silver plating slurry for low temperature co-fired ceramics, comprising the following steps:
[0019] S1. Preparing glass frit powder: placing glass frit in a ball mill, adding anhydrous ethanol to ball mill, drying under temperature control, and then placing in a muffle furnace to heat up to the melting temperature, keeping the temperature, quenching with water, and then ball milling, and drying under temperature control to obtain glass frit powder;
[0020] S2, preparing mixed material A: mixing the nano additive and the solvent evenly, adding the binder while stirring at controlled temperature, stirring evenly, and cooling to room temperature to obtain mixed material A;
[0021] S3, preparing a finished silver paste: silver powder, glass frit powder and mixed material A are stirred at a controlled speed to obtain mixed material B, and mixed material B is rolled into a paste slurry until the slurry fineness reaches the requirement of screen printing to obtain a finished silver paste.
[0022] As a preferred technical solution of the present invention, the ball milling time in step S1 is 12-18 hours, the temperature of the temperature-controlled drying is 80-90° C., and the time is 6-10 hours; and the insulation time is 2-3 hours.
[0023] As a preferred technical solution of the present invention, the temperature of the temperature control in step S2 is 70-75°C.
[0024] As a preferred technical solution of the present invention, the speed of the controlled stirring in step S3 is 1000-1100 r / min, and the time is 10-15 min.
[0025] Beneficial effects of the present invention:
[0026] (1) The present invention uses a compound of barium titanate, titanium dioxide and zinc oxide as nano-additives, which delays the sintering time of the slurry, reduces the shrinkage rate of the silver paste, effectively keeps the shrinkage of the silver paste consistent with that of the medium, and solves the problem of microcracks and warping caused by different shrinkage rates between materials during the sintering process.
[0027] (2) The glass material prepared under the specific raw material composition and ratio of the present invention can produce synergistic effects between its components to meet the low-temperature co-fired ceramic process conditions. At the same time, boron trioxide and silicon dioxide as glass network forming bodies can build a dense glass network structure, while barium oxide and strontium oxide as network modifiers can participate in the network structure and adjust the stability of the network structure. In addition, lanthanum oxide effectively stabilizes silver ions, and bismuth trioxide plays a role in buffering chemically corrosive substances. Therefore, the silver paste product prepared thereby has excellent chemical resistance. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] A chemical-resistant silver plating paste for low-temperature co-fired ceramics, the chemical-resistant silver plating paste comprising the following raw materials in parts by weight:
[0031]
[0032] The glass material comprises boron trioxide, silicon dioxide, bismuth trioxide, aluminum trioxide, strontium oxide, lanthanum oxide, barium oxide and strontium carbonate in a mass ratio of 15:12.5:4:3:2:1.5:0.8:0.5.
[0033] The nano additive comprises barium titanate with a particle size of 80 nm, titanium dioxide with a particle size of 90 nm, and zinc oxide with a particle size of 100 nm in a mass ratio of 3:5:3;
[0034] The binder comprises polyvinyl pyrrolidone and polyacrylate in a mass ratio of 1:1.2;
[0035] The solvent comprises butyl carbitol and terpineol in a mass ratio of 3:1.5.
[0036] A method for preparing a chemical silver plating slurry for low temperature co-fired ceramics, comprising the following steps:
[0037] S1. Preparation of glass frit powder: placing glass frit in a ball mill, adding anhydrous ethanol and ball milling for 18 h, drying at 85°C for 10 h, then placing in a muffle furnace and heating to the melting temperature, keeping the temperature for 3 h, quenching with water, ball milling for 15 h, and drying at 90°C for 6 h to obtain glass frit powder;
[0038] S2, preparing mixed material A: mixing the nano additive and the solvent evenly, adding the binder while stirring at 75°C, stirring evenly, and cooling to room temperature to obtain mixed material A;
[0039] S3, preparing finished silver paste: silver powder, glass frit powder and mixture A are stirred at a controlled speed of 1050 r / min for 15 min to obtain mixture B, and mixture B is rolled into a paste slurry until the slurry fineness reaches the requirement of screen printing to obtain a finished silver paste.
[0040] Example 2
[0041] A chemical-resistant silver plating paste for low-temperature co-fired ceramics, the chemical-resistant silver plating paste comprising the following raw materials in parts by weight:
[0042]
[0043] The glass material comprises boron trioxide, silicon dioxide, bismuth trioxide, aluminum trioxide, strontium oxide, lanthanum oxide, barium oxide and strontium carbonate in a mass ratio of 20:10:5:5:3:1:0.5:1.
[0044] The nano additive comprises barium titanate with a particle size of 100 nm, titanium dioxide with a particle size of 100 nm and zinc oxide with a particle size of 80 nm in a mass ratio of 5.5:4:4.5;
[0045] The binder comprises polyvinyl pyrrolidone and polyacrylate in a mass ratio of 1:1.4;
[0046] The solvent comprises butyl carbitol and terpineol in a mass ratio of 4:1.
[0047] A method for preparing a chemical silver plating slurry for low temperature co-fired ceramics, comprising the following steps:
[0048] S1. Preparation of glass frit powder: placing glass frit in a ball mill, adding anhydrous ethanol and ball milling for 12 h, drying at 90° C. for 8 h, then placing in a muffle furnace and heating to the melting temperature, keeping the temperature for 2.5 h, quenching with water, ball milling for another 12 h, and drying at 80° C. for 10 h to obtain glass frit powder;
[0049] S2, preparing mixed material A: mixing the nano additive and the solvent evenly, adding the binder while stirring at 70°C, stirring evenly, and cooling to room temperature to obtain mixed material A;
[0050] S3. Prepare finished silver paste: Stir silver powder, glass frit powder and mixture A at a controlled speed of 1100 r / min for 12.5 min to obtain mixture B, and roll mixture B into a paste slurry until the slurry fineness reaches the requirement of screen printing to obtain a finished silver paste.
[0051] Example 3
[0052] A chemical-resistant silver plating paste for low-temperature co-fired ceramics, the chemical-resistant silver plating paste comprising the following raw materials in parts by weight:
[0053]
[0054] The glass material comprises boron trioxide, silicon dioxide, bismuth trioxide, aluminum trioxide, strontium oxide, lanthanum oxide, barium oxide and strontium carbonate in a mass ratio of 17.5:15:6:4:2.5:2:0.65:0.75.
[0055] The nano additive comprises barium titanate with a particle size of 90 nm, titanium dioxide with a particle size of 80 nm and zinc oxide with a particle size of 90 nm in a mass ratio of 8:6:6;
[0056] The binder comprises polyvinyl pyrrolidone and polyacrylate in a mass ratio of 1:1;
[0057] The solvent comprises butyl carbitol and terpineol in a mass ratio of 3.5:2.
[0058] A method for preparing a chemical silver plating slurry for low temperature co-fired ceramics, comprising the following steps:
[0059] S1. Preparation of glass frit powder: placing glass frit in a ball mill, adding anhydrous ethanol and ball milling for 18 h, drying at 85°C for 10 h, then placing in a muffle furnace and heating to the melting temperature, keeping the temperature for 3 h, quenching with water, ball milling for 15 h, and drying at 90°C for 6 h to obtain glass frit powder;
[0060] S2, preparing mixed material A: mixing the nano additive and the solvent evenly, adding the binder while stirring at 75°C, stirring evenly, and cooling to room temperature to obtain mixed material A;
[0061] S3, preparing finished silver paste: silver powder, glass frit powder and mixture A are stirred at a controlled speed of 1050 r / min for 15 min to obtain mixture B, and mixture B is rolled into a paste slurry until the slurry fineness reaches the requirement of screen printing to obtain a finished silver paste.
[0062] Comparative Example 1
[0063] Compared with Example 3, the difference is that barium titanate is not added to the nano-additive of Comparative Example 1, and titanium dioxide with half the mass of barium titanate and zinc oxide with half the mass of barium titanate are used instead, and the other operating steps and parameters remain unchanged.
[0064] Comparative Example 2
[0065] Compared with Example 3, the difference is that titanium dioxide is not added to the nano-additive of Comparative Example 2, and barium titanate with half the mass of titanium dioxide and zinc oxide with half the mass of titanium dioxide are used instead, and the other operating steps and parameters remain unchanged.
[0066] Comparative Example 3
[0067] Compared with Example 3, the difference is that zinc oxide is not added to the nano additive of Comparative Example 3, and barium titanate with half the mass of zinc oxide and titanium dioxide with half the mass of zinc oxide are used instead, and the other operating steps and parameters remain unchanged.
[0068] Comparative Example 4
[0069] Compared with Example 3, the difference is that barium oxide is not added to the glass material of Comparative Example 4, and strontium oxide, lanthanum oxide and bismuth trioxide with 1 / 3 of the mass of barium oxide are used instead, and the other operating steps and parameters remain unchanged.
[0070] Comparative Example 5
[0071] Compared with Example 3, the difference is that strontium oxide is not added to the glass material of Comparative Example 5, and barium oxide, lanthanum oxide and bismuth trioxide with 1 / 3 the mass of strontium oxide are used instead, and the other operating steps and parameters remain unchanged.
[0072] Comparative Example 6
[0073] Compared with Example 3, the difference is that lanthanum oxide is not added to the glass material of Comparative Example 6, and barium oxide, strontium oxide and bismuth trioxide with 1 / 3 of the mass of lanthanum oxide are used instead, and the other operating steps and parameters remain unchanged.
[0074] Comparative Example 7
[0075] Compared with Example 3, the difference is that bismuth trioxide is not added to the glass material of Comparative Example 7, and barium oxide, strontium oxide and lanthanum oxide with 1 / 3 of the mass of bismuth trioxide are used instead, and the other operating steps and parameters remain unchanged.
[0076] Test Example 1
[0077] The finished silver pastes obtained in Examples 1-3 and Comparative Examples 1-3 were respectively printed on LTCC substrates (purchased from the 43rd Institute of China Electronics Technology Group Corporation) by screen printing to form silver films of 10 mm*10 mm in size, and then dried at 90°C for 45 min, then heated to 400°C at a heating rate of 10°C / min in an air atmosphere and kept warm for 1 h, and finally heated to 900°C at a heating rate of 10°C / min in a nitrogen atmosphere and kept warm for 1 h, and naturally cooled to room temperature to obtain sintered silver films with a thickness of 8 μm. The same producer observed whether microcracks and warping occurred on the surface of the sintered silver film, and the results are shown in Table 1.
[0078] Table 1
[0079] Whether micro cracks or warping occurs Example 1 no Example 2 no Example 3 no Comparative Example 1 yes Comparative Example 2 yes Comparative Example 3 yes
[0080] It can be seen from Table 1 that the silver paste product prepared by the present invention can effectively solve the problem of micro cracks and warping caused by different shrinkage rates between materials during the re-sintering process.
[0081] Test Example 2
[0082] The finished silver pastes prepared in Examples 1-3 and Comparative Examples 4-7 were respectively printed on LTCC substrates (purchased from the 43rd Institute of China Electronics Technology Group Corporation) by screen printing, and sintered at 850° C. The sintered substrates were respectively immersed in a 10% HCl solution and a 10% NaOH solution at 25° C. for 30 min. The surface flatness and acid and alkali resistance of the silver film layer were tested. The surface flatness ≤0.2 mm / 50 mm was qualified. The results are shown in Table 2.
[0083] Table 2
[0084]
[0085] It can be seen from Table 2 that the silver paste product prepared by the present invention has excellent chemical resistance.
[0086] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0087] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A chemical silver plating slurry for low temperature co-fired ceramics, characterized in that: The chemical silver plating slurry comprises the following raw materials in parts by weight:
2. The chemical silver plating slurry for low temperature co-fired ceramics according to claim 1, characterized in that: The glass material includes boron trioxide, silicon dioxide, bismuth trioxide, aluminum trioxide, strontium oxide, lanthanum oxide, barium oxide, and strontium carbonate.
3. The chemical silver plating slurry for low temperature co-fired ceramics according to claim 2, characterized in that: The mass ratio of boron trioxide, silicon dioxide, bismuth trioxide, aluminum trioxide, strontium oxide, lanthanum oxide, barium oxide and strontium carbonate is 15-20:10-15:4-6:3-5:2-3:1-2:0.5-0.8:0.5-1.
4. The chemical silver plating slurry for low temperature co-fired ceramics according to claim 1, characterized in that: The nano additives include barium titanate, titanium dioxide and zinc oxide.
5. The chemical silver plating slurry for low temperature co-fired ceramics according to claim 4, characterized in that: The mass ratio of the barium titanate, titanium dioxide and zinc oxide is 3-8:4-6:3-6.
6. The chemical silver plating slurry for low temperature co-fired ceramics according to claim 1, characterized in that: The binder includes polyvinyl pyrrolidone and polyacrylate.
7. The chemical silver plating resistant paste for low temperature co-fired ceramics according to claim 6, characterized in that: The mass ratio of the polyvinyl pyrrolidone to the polyacrylate is 1:1-1.
4.
8. The chemical silver plating resistant paste for low temperature co-fired ceramics according to claim 1, characterized in that: The solvents include butyl carbitol and terpineol.
9. The chemical silver plating slurry for low temperature co-fired ceramics according to claim 8, characterized in that: The mass ratio of butyl carbitol to terpineol is 3-4:1-2.
10. A method for preparing a chemical silver plating resistant paste for low temperature co-fired ceramics according to any one of claims 1 to 9, characterized in that: The specific steps include: S1. Preparing glass frit powder: placing glass frit in a ball mill, adding anhydrous ethanol to ball mill, drying under temperature control, and then placing in a muffle furnace to heat up to the melting temperature, keeping the temperature, quenching with water, and then ball milling, and drying under temperature control to obtain glass frit powder; S2, preparing mixed material A: mixing the nano additive and the solvent evenly, adding the binder while stirring at controlled temperature, stirring evenly, and cooling to room temperature to obtain mixed material A; S3, preparing a finished silver paste: silver powder, glass frit powder and mixed material A are stirred at a controlled speed to obtain mixed material B, and mixed material B is rolled into a paste slurry until the slurry fineness reaches the requirement of screen printing to obtain a finished silver paste.